Majoritic garnet grains within shock-induced melt veins in amphibolites from the Ries impact crater suggest ultrahigh crystallization pressures between 18 and 9 GPa - Stähle, Volker; Altherr, Rainer; Trieloff, Mario; Varychev, Alexander (Contributions to mineralogy and petrology, 2017)
Shock-induced melt veins in amphibolites from the Nördlinger Ries often have chemical compositions that are similar to bulk rock (i.e., basaltic), but there are other veins that are confined to chlorite-rich cracks that formed before the impact and these are poor in Ca and Na. Majoritic garnets within the shock veins show a broad chemical variation between three endmembers: ( (1) VIIIM2+3VIAl2(IVSiO4)3 (normal garnet, Grt), (2) VIIIM2+3VI[M2+(Si,Ti)](IVSiO4)3 (majorite, Maj), and (3) VIII(NaM2+2)VI[(Si,Ti)Al](IVSiO4)3 (Na-majorite50Grt50), whereby M2+ = Mg2+, Fe2+, Mn2+, Ca2+. In particular, we observed a broad variation in VI(Si,Ti) which ranges from 0.12 to 0.58 cations per formula unit (cpfu). All these majoritic garnets crystallized during shock pressure release at different ultrahigh pressures. Those with high VI(Si,Ti) (0.36-0.58 cpfu) formed at high pressures and temperatures from amphibole-rich melts, while majoritic garnets with lower VI(Si,Ti) of 0.12-0.27 cpfu formed at lower pressures and temperatures from chlorite-rich melts. Furthermore, majoritic garnets with intermediate values of VI(Si,Ti) (0.24-0.39) crystallized from melts with intermediate contents of Ca and Na. To the best of our knowledge the ‘MORB-type’ Ca-Na-rich majoritic garnets with maximum contents of 2.99 wt% Na2O and calculated crystallisation pressures of 16-18 GPa are the most extreme representatives ever found in terrestrial shocked materials. At the Ries, the duration of the initial contact and compression stage at the central location of impact is estimated to only ~ 0.1 s. We used a ~ 200-µm-thick shock-induced vein in a moderately shocked amphibolite to model its pressure-temperature-time (P-T-t) path. The graphic model manifests a peak temperature of ~ 2600 °C for the vein, continuum pressure lasting for ~ 0.02 s, a quench duration of ~ 0.02 s and a shock pulse of ~ 0.038 s. The small difference between the continuum pressure and the pressure of majoritic garnet crystallization underlines the usefulness of applying crystallisation pressures of majoritic garnets from metabasites for calculation of dynamic shock pressures of host rocks. Majoritic garnets of chlorite provenance, however, are not suitable for the determination of continuum pressure since they crystallized relatively late during shock release. An extraordinary glass- and majorite-bearing amphibole fragment in a shock-vein of one amphibolite documents the whole unloading path.
Gesehen am 09.08.2018
Im Titel ist die Zahl "9" tiefgestellt